2018
DOI: 10.1097/cin.0000000000000450
|View full text |Cite
|
Sign up to set email alerts
|

What to Consider in a Culturally Tailored Technology-Based Intervention?

Abstract: The purpose of this article is to identify practical issues in implementing a culturally tailored technology-based intervention among Asian American survivors of breast cancer. In a large-scale technology-based breast cancer intervention study, research team members wrote memos on issues in implementing a culturally tailored technology-based intervention and plausible reasons for the issues. Then, the content of the research diaries was analyzed, along with written records of the research team. The practical i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 42 publications
1
17
0
Order By: Relevance
“…“We suggest developing a protocol for standardized interventions that includes regular training of staff members, through which intervention quality could be maintained despite varying competencies among intervention staff” (Im et al 2018 , p. 432)…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…“We suggest developing a protocol for standardized interventions that includes regular training of staff members, through which intervention quality could be maintained despite varying competencies among intervention staff” (Im et al 2018 , p. 432)…”
Section: Methodsmentioning
confidence: 99%
“…Studies gave several reasons for low attendance and high attrition rates of participants. Most participants came from underserved populations with low incomes and had limited access to transportation, inhibiting their ability to attend intervention sites (Burkart et al, 2017;Im et al 2018). Bernard-Davila et al, 2015) and Burkart et al (2017) demonstrated that sustained interventions created a burden on participants who had to work for their living.…”
Section: Low Attention and Retention Ratesmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, a randomized repeated measures control group design was adopted. This was a part of a larger ongoing study that examines the efficacy of a culturally tailored technology-based information and coaching/support program on survivorship experience of Asian American breast cancer survivors (Im et al, 2018(Im et al, , 2019Im, Kim, Yang, & Chee, 2020;Im et al, 2017). The study was approved by the Institutional Review Board of the authors' institution.…”
Section: Methodsmentioning
confidence: 99%
“…Again, all the intervention components were accessed through computers, mobile devices, and tablets. More detailed information on the intervention is available elsewhere (Im et al, 2018(Im et al, , 2019Im, Kim, Xu et al, 2020;Im et al, 2017).…”
Section: The Technology-based Programmentioning
confidence: 99%